Analysis of Inventory Management and Distribution Costs in Improving Profitability at Cirejag Mushroom Agency - Arum, Mirah Sekar; Fadli, Uus Mohammad Darul; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
Inventory management and distribution costs are important factors in maintaining a company’s profitability. This study was conducted to identify, calculate, analyze, and explain the levels of inventory management, distribution costs, and profitability at Agen Jamur Cirejag Karawang. A quantitative descriptive method was used with data sourced from purchase records and distribution costs from October 2024 to September 2025. Data was obtained through interviews, observations, and documentation with business owners who were the main informants for the research. The research was conducted at the Cirejag Mushroom Agency, CV Langgeng Jaya, in Cirejag Village, Jatisari, Karawang Regency, West Java. Inventory management was analyzed using the Economic Order Quantity, Reorder Point, and Safety Stock methods, while distribution costs were calculated based on all transportation and storage costs. Business profitability was measured using the Net Profit Margin (NPM). The results showed that enoki mushroom inventory management was not optimal because the frequency of orders was too high. The application of the EOQ method to enoki mushrooms has the potential to reduce ordering costs by Rp 107.216.667/year. In addition, distribution costs are relatively high and have not been managed systematically, thereby reducing business profits. Profitability calculations show an NPM value of 0,59%, with net profits still relatively low compared to total sales.